(untitled) (Fiep Bulletin - online, 2015)
As all city, Rinópolis historicamente passed for transformations politics, social, cultural and mainly economic. Exactly thus, they come searching to conserve its values strong pautados by the religion catholic, being that one of its more excellent cultural traces is its religious parties. Ahead of this scene, a significant part of the community always was mobilized when the subject was the celebration of on dates to the Church Catholic. È in this direction that quermesse it if became one practical social and cultural gift in the most important celebrations carried through catholics. Searching to tread the necessary ways to the research it is that we assume these parties as moments of magic and wealth, a full exercise of the imaginary one. In this context we understand to be it quermesse an excellent existing cultural manifestation in the city, where we identify the social representations that the involved actors directly with the party elaborate on it. With this objective, we take as research the traditional one quermesse in homage Is Cristóvão carried through in days 24 and 25 of July of 2004.